Pengembangan Bahan ajar Berbasis Word Square Untuk Meningkatkan Hasil Belajar Tematik - Fauziana, Fauziana; Dewi Saputri, Rikei; Zulaiha, Siti; Riyan Oktori, Agus (Genderang Asa: Journal of Primary Education, 2023)
Teaching materials based on Word Square are instructional modules designed as a game to enhance students' abilities in answering questions and finding suitable answers within answer squares. This game encourages students to be more careful, independent, and meticulous. The aim of this research is to assess the development, feasibility, and effectiveness of Word Square teaching materials in improving thematic learning outcomes for third-grade students at SDN 4 Rejang Lebong. The study adopts the Research and Development (R&D) approach, following the Borg and Gall research procedure, encompassing potential problems, data collection, product design, design validation, design revision, product testing, product revision, and usage testing. The research employs pre-test and post-test assessments with the same group to gauge children's understanding of using Word Square teaching materials. The analysis reveals that teachers express an 88.64% need, categorized as "required," while students show a 93.33% need, also categorized as "required." Validation results from content experts indicate 88.89% as "highly suitable," language experts at 86.61% as "highly suitable," and media experts at 93.18% as "highly suitable." Both qualitative and quantitative data analysis techniques were utilized. The findings indicate that the Word Square teaching material is suitable for use, falling under the "highly suitable" category, fostering active, independent, and effective learning. The comprehension level, scored at 95.54, falls within the "effective" category.